RELEVANCE OF RELIGIOUS LEXICOLOGY IN ENGLISH LANGUAGE (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Religious lexicology reveals the historical development and cultural context of the English language. Religious terms represent the connection between language and society, and occupy an important place in multiculturalism and interreligious communication. This article analyzes the importance of religious lexicology and its influence on the modern language.